PENERAPAN METODE INTENSIVE READING UNTUK MENINGKATKAN PEMAHAMAN SISWA TERHADAP TEKS BERBAHASA PERANCIS TINGKAT A1 DELF : Studi Pra-Eksperimental terhadap Siswa Kelas XII Semester IISMAN 6 Cimahi Tahun Akademik 2013/2014 - Ramdhani, Dani (2014)
Membacapemahamanmerupakansalahsatujenismembacadalamhati.PenelitianinimembahastentangpenerapanmetodeIntensive Reading untukmeningkatkanpemahamansiswaterhadapteksberbahasaPerancistingkat A1 DELF.Penelitianinibertujuanuntukmemperoleh data tentang : 1) tingkatkemampuanmembacapemahamansiswasebelumdansesudahditerapkannyametodeIntensive reading ; 2) keefektifanmetodeIntensive reading dalammeningkatkanpemahamansiswaterhadapteksberbahasaPerancistingkat A1 DELF ; 3) kelebihandankekurangandaripenerapanmetodeIntensive reading dalampembelajaranmembacapemahamanteksberbahasaPerancistingkat A1 DELF. Sampeldaripenelitianiniialah 20 orang siswa SMA Negeri 6 Cimahitahunajaran 2013/2014.Metode yang digunakandalampenelitianiniadalahpre-experimental dengandesainpenelitianone group pretest-posttest.Teknikpengumpulandatanyayaitudenganmenggunakantes, angketdanobservasi.HasilpenelitianinimenunjukkanbahwametodeIntensive reading iniefektifditerapkandalampembelajaranmembacapemahamanteksberbahasaPerancistingkat A1 DELF. Reading comprehension is a kind of silent reading. This study discusses about the implementation of Intensive Reading to improve student understanding a text in frenchat level A1 DELF. The aims of this research are to obtain data on: 1) the levels of reading comprehension ability of the student before and after the application of intensive reading method; 2) the effectiveness of intensive reading method for improving students understanding a text in French at level A1 DELF; 3) the advantages and disadvantages of implementation intensive reading method in learningFrench text comprehension at level A1 DELF. The samples of this study are reading skill of 20 students of SMAN 6 Cimahiof school year 2013/2014. The methodis pre-experimental with a research design of one group pretest-posttest. The techniques of collecting data are test, questionnaires and observation. The result of this study show that intensive reading method is effective to be applied in learning a french text level A1 DELF reading comprehension.